2005
DOI: 10.1016/j.brainresbull.2005.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of methamphetamine-induced behavioral sensitization in mice by systemic administration of naltrexone

Abstract: Repeated intermittent exposure to psychostimulants was found to produce behavioral sensitization. The present study was designed to establish a mouse model and by which to investigate whether opioidergic system plays a role in methamphetamine-induced behavioral sensitization. Mice injected with 2.5 mg/kg of methamphetamine once a day for 7 consecutive days showed behavioral sensitization after challenge with 0.3125 mg/kg of the drug on day 11, whereas mice injected with a lower daily dose (1.25 mg/kg) did not.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 57 publications
2
45
1
Order By: Relevance
“…Pretreatment with the opiate antagonist naltrexone abolished food-conditioned activity in FR animals, whereas it had little effect on the activity of controls, suggesting that opioid receptors are involved in the expression of food-induced sensitization. We are unaware of data on the effects of opioid blockade on the expression of cocaine sensitization, although naltrexone blocks the expression of behavioral sensitization to methamphetamine (Chiu et al, 2005). The ability of another opioid antagonist, naloxone, to decrease operant responding for food reinforcers (Glass et al, 1999) and food-conditioned locomotor activity in the presence of food (Hayward and Low, 2005), as well as the ability of the -agonist morphine to induce context-dependent conditioned feeding (Kelley et al, 2000) suggests a role for opiate receptors in food-conditioned responses.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with the opiate antagonist naltrexone abolished food-conditioned activity in FR animals, whereas it had little effect on the activity of controls, suggesting that opioid receptors are involved in the expression of food-induced sensitization. We are unaware of data on the effects of opioid blockade on the expression of cocaine sensitization, although naltrexone blocks the expression of behavioral sensitization to methamphetamine (Chiu et al, 2005). The ability of another opioid antagonist, naloxone, to decrease operant responding for food reinforcers (Glass et al, 1999) and food-conditioned locomotor activity in the presence of food (Hayward and Low, 2005), as well as the ability of the -agonist morphine to induce context-dependent conditioned feeding (Kelley et al, 2000) suggests a role for opiate receptors in food-conditioned responses.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that repeated use of MAP induces addiction (Hyman 1996), sensitization (Chiu et al 2005;Shuto et al 2006), and those may cause deficits in memory and learning (Vorhees et al 2007;Lundqvist 2005). The major toxic effects of MAP involve disturbance of dopaminergic pathways (Daberkow et al 2005;Kish 2008;Gerra et al 2003), which leads to behavioral sensitization, which is a progressive and enduring increase in locomotor activity coupled with stereotypic behavior (Robinson and Becker 1986).…”
Section: Introductionmentioning
confidence: 98%
“…Naltrexone (NTX) is an opioid receptor antagonist with empirically supported efficacy and FDA approval for the treatment of alcoholism (Anton et al, 2006;O'Malley et al, 1992;Volpicelli et al, 1992) and opioid dependence (Cornish et al, 1997). Preclinical models suggest that NTX may also affect MA use, as NTX attenuated MA-induced sensitization (Chiu et al, 2005), amphetamine drug-seeking reinstatement (Haggkvist et al, 2008), and cue-induced MA seeking in rodents (Anggadiredja et al, 2004). In particular, preclinical studies suggested that μ-opioid (Chiu et al, 2006) and δ-opioid (Suzuki et al, 1997) receptors may underlie MA-induced behavioral sensitization, analogous to compulsive drug-seeking behavior in humans (ie, drug craving; Itzhak and Ali, 2002), through its modulatory actions of the mesolimbic dopamine system (Ford et al, 2006).…”
Section: Introductionmentioning
confidence: 99%